The magic of ballroom dancing [videorecording (DVD)] capture the magic and learn to dance from the pros. - Mason, Teresa; Turley, Kyle; Turley, Heather (Heather Menard Turley) (Kultur, 2012)
Presents a comprehensive introduction to ballroom dancing, featuring Teresa Mason's method to teach beginning-, intermediate-, and advanced-level dancers, and covering frame, leading, dance positions, and related topics with tips and advice from Teresa Mason.